A systematic review on the extant of outdoor advertisements literature in developing countries - Mwilongo, Kardo; Swallehe, Omary (Open journal of business and management, 2024)
A research paper submitted to the open journal of business and management, Vol. 10, of 2022, Pg. 1676-1694